The Importance of Strategic Planning on Leather Company UD Nogosari Leather in Lumajang Regency - GAHTAN THORIQ (Jurnal Ilmiah Mahasiswa FEB, 2017)
The tannery industry is an industry that always experiences developmental and environmental changes all the time, so UD. Nogosari Leather need to plan a strategy for keeping the stand in the Indonesia tannery industry. The type of the research is descriptive and the data collection technique are observation, interview, questionnaire, and documentation. This research used IFE matrix, EFE matrix, SWOT matrix, Grand Strategy matrix, IE matrix, and QSPM matrix as the analysis technique.The results show that UD. Nogosari Leather position is above average so the company has the capability to optimize its strengths and overcome its weaknesses. Besides that, UD. Nogosari Leather can find a solution for anticipating the threat by responding to all of the opportunities that prevailed.  Based on the QSPM matrix, horizontal integration can be applied as the company strategy. Keywords : internal environment, external environment, strategic plan, IFE matrix, EFE matrix, SWOT matrix, grand strategy, IE matrix,  QSPM matrix.